2019
DOI: 10.3892/ol.2019.10431
|View full text |Cite
|
Sign up to set email alerts
|

A novel CpG island methylation panel predicts survival in lung adenocarcinomas

Abstract: The lack of clinically useful biomarkers compromise the personalized management of lung adenocarcinomas (ADCs); epigenetic events and DNA methylation in particular have exhibited potential value as biomarkers. By comparing genome-wide DNA methylation data of paired lung ADCs and normal tissues from 6 public datasets, cancer-specific CpG island (CGI) methylation changes were identified with a pre-specified criterion. Correlations between DNA methylation and expression data for each gene were assessed by Pearson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…A number of researches have also been done to identify cancerspecific DNA methylation markers in lung cancer patients. Yan et al [54] identified a panel with nine CpGs using a combined public methylation datasets and constructed a prognosis model to predict survival in LUAD patients. Diaz-Lagares et al [13] identified four methylation markers including BCAT1, CDO1, TRIM58, and ZNF177 and achieved 85% AUC on a regression model trained from the combination of four markers in bronchoalveolar lavages from patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of researches have also been done to identify cancerspecific DNA methylation markers in lung cancer patients. Yan et al [54] identified a panel with nine CpGs using a combined public methylation datasets and constructed a prognosis model to predict survival in LUAD patients. Diaz-Lagares et al [13] identified four methylation markers including BCAT1, CDO1, TRIM58, and ZNF177 and achieved 85% AUC on a regression model trained from the combination of four markers in bronchoalveolar lavages from patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al . [54] identified a panel with nine CpGs using a combined public methylation datasets and constructed a prognosis model to predict survival in LUAD patients. Diaz‐Lagares et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, survival multivariate analyses were not evaluated for these probes. This multivariate approach has already been conducted for clear cell renal carcinoma [ 59 ], leukemia [ 60 ], esophageal squamous cell carcinoma [ 61 ], colorectal cancer [ 62 ], lung adenocarcinoma [ 63 ], among others. Future validation of the identified CpGs methylation panels in a new cohort will be deemed necessary for their use in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, autosomal-chromosome-encoded paralogs of X chromosome-linked RPs have strong expression bias for the male germ cell lineage, where they have been linked to highly specialized functions: RPL10L takes over the function of RPL10 upon X chromosome inactivation in the meiotic phase of spermatogenesis 3 , and RPL39L was implicated in the translation of long-lived, sperm cell-specific proteins 4 . However, the RPL39L mRNA was also observed in other cell types, including ovarian 5 and breast cancers 2 , as well as in lung cancer 6 and neuroblastoma 4 cell lines. Gene amplifications 7 and the hypomethylation of a specific CpG island 6 were proposed as mechanisms underlying RPL39L expression in cancers.…”
Section: Introductionmentioning
confidence: 94%
“…However, the RPL39L mRNA was also observed in other cell types, including ovarian 5 and breast cancers 2 , as well as in lung cancer 6 and neuroblastoma 4 cell lines. Gene amplifications 7 and the hypomethylation of a specific CpG island 6 were proposed as mechanisms underlying RPL39L expression in cancers. These observations suggest that RPL39L has a general function, extending beyond the translation of long-lived sperm cell proteins.…”
Section: Introductionmentioning
confidence: 94%